The Influence of Capital Structure, Productive Assets, and Intellectual Capital on Financial Performance in Manufacturing Companies (Case Study: Consumer Goods Sector Listed on the Indonesia Stock Exchange, 2020–2024) - Krisjayanti, Krisjayanti; Hermanto, Bambang (IJOSPOL - International Journal of Social, Policy and Law, 2026)
Manufacturing companies play a strategic role in the national economy; therefore, financial performance is a key indicator in assessing corporate success, which is influenced by various internal factors such as capital structure, productive asset management, and the utilization of intellectual capital. The period 2020–2024 was marked by economic uncertainty that required companies to manage resources optimally in order to maintain sound financial performance. This study is grounded in capital structure theory, asset efficiency theory, and the concept of intellectual capital, which comprises human capital, structural capital, and capital employed, with financial performance measured using financial indicators that reflect a company’s ability to generate profits and manage resources efficiently. The research employs a quantitative approach using secondary data in the form of financial statements of manufacturing companies in the consumer goods sektor listed on the Indonesia Stock Exchange during the 2020–2024 period, analyzed using multiple linear regression through partial hypothesis testing (t-test) and simultaneous testing (F-test). The results show that capital structure has a significant negative effect on financial performance, indicating that excessive use of debt can reduce a company’s financial performance, while productive assets have a significant positive effect, suggesting that effective asset management can enhance financial performance. In addition, intellectual capital also has a significant negative effect on financial performance, indicating that increases in intellectual capital have not yet been fully accompanied by optimal management. Simultaneously, capital structure, productive assets, and intellectual capital have a significant effect on the financial performance of manufacturing companies.